A Role of Fluoride on Free Radical Generation and Oxidative Stress in BV-2 Microglia Cells. (13th August 2012) - Shuhua, Xi; Ziyou, Liu; Ling, Yan; Fei, Wang; Sun, Guifan
Abstract : The generation of ROS and lipid peroxidation has been considered to play an important role in the pathogenesis of chronic fluoride toxicity. In the present study, we observed that fluoride activated BV-2 microglia cell line by observing OX-42 expression in immunocytochemistry. Intracellular superoxide dismutase (SOD), glutathione (GSH), malondialdehyde (MDA), reactive oxygen species (ROS), superoxide anions (O 2 ∙ - ), nitric oxide synthase (NOS), nitrotyrosine (NT) and nitric oxide (NO), NOS in cell medium were determined for oxidative stress assessment. Our study found that NaF of concentration from 5 to 20 mg/L can stimuli BV-2 cells to change into activated microglia displaying upregulated OX-42 expression. SOD activities significantly decreased in fluoride-treated BV-2 cells as compared with control, and MDA concentrations and contents of ROS andO 2 ∙ - increased in NaF-treated cells. Activities of NOS in cells and medium significantly increased with fluoride concentrations in a dose-dependent manner. NT concentrations also increased significantly in 10 and 50 mg/L NaF-treated cells compared with the control cells. Our present study demonstrated that toxic effects of fluoride on the central nervous system possibly partly ascribed to activiting of microglia, which enhanced oxidative stress induced by ROS and reactive nitrogen species.